MAJLIS TAFSIR AL-QURAN DAN KEBERAGAMAAN DI INDONESIA: STUDI TENTANG PERAN DAN KEDUDUKAN HADIS MENURUT MTA - Muhammad Alfatih Suryadilaga (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2015)
Social development of Muslim society in Indonesia related to the study of hadith seems quite dynamic. Each organization has its own characteristics in defining and positioning hadith as the second of Islamic authority after Quran, such as the Majlis Tafsir Al-Quran (MTA). The problem begun since there is a research mentioning that MTA is almost considered not positioning hadith as explanatory of Quran. It is dealing with the MTA jargon its self, returning to the Quran and sunnah shahihah. This article discusses about how MTA, which is currently led by Ahmad Sukino, positions the hadith as the second of Islamic authority after Quran. In addition, MTA states that only sunah shahihah can be used as dalil or hujjah. MTA also distinguishes human cultural behaviors with pure religious behaviors as they are generally called ibadah. Thus, for MTA, no ibadah except there is nash sharih, both from the Quran and sunnah. Then, when we read more deeply and critically, MTA is actually inconsistent in understanding and practicing Islam textually, but sometimes they use the fikih and usul fikih as a means to analyse the Quran and hadith.Keywords: MTA, Textualist, Hadith, Islamic Authority